Strategies for the molecular genetic manipulation and visualization of the human fungal pathogen Penicillium marneffei - Kylie J. Boyce; Hayley E. Bugeja; Harshini Weerasinghe; Michael J. Payne; Lena Schreider (Fungal Genetics Reports, 2012)
P. marneffei has been established as an experimentally amenable system to study morphogenesis and pathogenicity. This paper describes the development of a number of tools, including numerous selectable markers, to expand the ease with which it can be genetically manipulated. Combined with strains engineered for homologous recombination of exogenous DNA, these tools facilitate efficient molecular genetic studies.